2013
DOI: 10.1155/2013/601768
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Pain, Functional Status, and Health-Related Quality of Life after Head and Neck Cancer Surgery

Abstract: Head and neck cancer (HNC) patients experience treatment-related complications that may interfere with health-related quality of life (HRQOL). The purpose of this study was to describe the symptom experience (shoulder pain) and functional status factors that are related to global and domain-specific HRQOL at one month after HNC surgery. In this exploratory study, we examined 29 patients. The outcome variables included global HRQOL as well as physical, functional, emotional, and social well-being. Symptom exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Recovery can be slow, with high rates of chronic pain; in a community‐based cohort, only 49% of respondents reported a complete recovery at 18 months 3. Shoulder pain has a significant negative impact on quality of life 4, 5, 6. It also poses a significant economic burden, with costs estimated to be £310 million in the first 6 months following primary care contact 7.
Significance & Innovations

The majority of studies show conflicting results on the association of imaging‐detected features with symptoms.

The majority of studies did not evaluate the role of multiple pathologies in shoulder symptoms.

Of the possible individual structures to be associated with pain, enlarging rotator cuff tears may be associated with incident symptoms.

…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery can be slow, with high rates of chronic pain; in a community‐based cohort, only 49% of respondents reported a complete recovery at 18 months 3. Shoulder pain has a significant negative impact on quality of life 4, 5, 6. It also poses a significant economic burden, with costs estimated to be £310 million in the first 6 months following primary care contact 7.
Significance & Innovations

The majority of studies show conflicting results on the association of imaging‐detected features with symptoms.

The majority of studies did not evaluate the role of multiple pathologies in shoulder symptoms.

Of the possible individual structures to be associated with pain, enlarging rotator cuff tears may be associated with incident symptoms.

…”
Section: Introductionmentioning
confidence: 99%
“…Recovery can be slow, with high rates of chronic pain; in a community-based cohort, only 49% of respondents reported a complete recovery at 18 months (3). Shoulder pain has a significant negative impact on quality of life (4)(5)(6). It also poses a significant economic burden, with costs estimated to be £310 million in the first 6 months following primary care contact (7).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, an estimated 45,780 HNSCCs (2.8 % of newly diagnosed cancer cases) and 8650 related deaths will have occurred in the US (Siegel et al 2015). Despite advances in the treatment of HNSCCs, treatment-related complications have a profound effect on a patient's quality of life, including impaired speech (Noonan and Hegarty 2010), difficulties with eating and breathing (Frowen and Perry 2006), permanent disfigurement (Callahan 2004), and chronic pain (Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In an another international study similar findings were observed on shoulder pain, functional status and HRQOL after HNC surgery and concluded that HNC patients who encountered shoulder pain, eating impairment, speaking impairment, and impaired body image which interfered with HRQOL during the early postoperative period [14]. The American Cancer Society in 2013 recommended early and regular assessment of symptoms and impaired body functions across the cancer care continuum [14].…”
Section: Discussionmentioning
confidence: 75%
“…The American Cancer Society in 2013 recommended early and regular assessment of symptoms and impaired body functions across the cancer care continuum [14]. Swallowing dysfunction were also evaluated by using endoscopic examination after radiotherapy in HNC patients [15].…”
Section: Discussionmentioning
confidence: 99%